Video-analiza za vrednotenje in popravljanje tehnike teka - Špenko, Matic (Šport (Ljubljana), 2019)
Evaluation and correction of running technique can significantly decrease injury risk in runners. Due to the expensiveness and time-consuming nature of 3D kinematic analysis, alternatives such as 2D video-analysis are often used. Recent research indicates good reliability of 2D video-analysis for assessment of joint angles during running, foot strike pattern and temporal description of phases in running cycle. Similarly, good validity of 2D video analysis was previously reported for evaluating foot strike pattern and hip position, while the results regarding pelvic drop and knee angle are equivocal. To increase the reliability and validity of measurements using 2D video analysis, it is recommended to maximize the video quality and use a set-up with good lighting, appropriate camera position, constant distance between camera and the runner, and good marking of anatomical bony landmarks.
Keywords: kinematics; kinematika; reliability; running; running cycle; sport; šport; tek; tekaški cikel; video analiza; video analysis; zanesljivost